2018
DOI: 10.3892/mco.2018.1611
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the kidney at the advanced stage: A case series of eight Chinese patients

Abstract: Abstract. Primitive neuroectodermal tumor (PNET) rarely occurs as a primary renal neoplasm. Renal (r)PNET is a rare but aggressive neoplasm with poor prognosis; the majority of patients are diagnosed as advanced stage at presentation and face a worse prognosis than patients with localized disease. The present study describes the diagnosis and management of eight cases of rPNET at an advanced stage, who were treated at two institutions [Lingnan Hospital (branch of The Third Affiliated Hospital) and the Cancer C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
6
2
Order By: Relevance
“…The presenting symptoms of renal PNET are nonspecific, including flank pain, abdominal mass, hematuria, and other symptoms related to genitourinary infections ( 9 ). A retrospective study done by Sun et al showed most patients (87%) having renal PNET on the left side, but our study and case series conducted by Narayanan et al revealed it to be on the right kidney in most of the patients ( 10 , 11 ).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The presenting symptoms of renal PNET are nonspecific, including flank pain, abdominal mass, hematuria, and other symptoms related to genitourinary infections ( 9 ). A retrospective study done by Sun et al showed most patients (87%) having renal PNET on the left side, but our study and case series conducted by Narayanan et al revealed it to be on the right kidney in most of the patients ( 10 , 11 ).…”
Section: Discussioncontrasting
confidence: 73%
“…In a retrospective study conducted by Sun et al, four cases received adjuvant chemotherapy. They had a significantly better overall survival of 36 months, compared with an overall survival of 10 months in the three patients without adjuvant chemotherapy ( 10 ). In the present study, one of the patients with the localized disease received chemotherapy, that is, VAC/IE of a total of 17 cycles and following up regularly with remission for the last 2 years and 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective treatment methods include a combination of surgery, chemotherapy and radiotherapy. VDC (vincristine, doxorubicin, cyclophosphamide) alternating with the use of IE (ifosphamide, VP-16) in combination is currently the recommended treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the EFT-2001 protocol, 1800 mg/m 2 of ifosfamide per day for 5 days and 100 mg/m 2 of etoposide per day for the same period are added to the VAC regimen (20). Sun et al studied the role of cytokine-induced killer (CIK) cell immunotherapy in a patient of renal PNET (10). They noted a survival advantage of 20 months with lesser adverse events with this form of therapy in comparison to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%